RHYTHM AND MELODY IN UZBEK LYRICS OF THE INDEPENDENCE PERIOD (Scientific journal of the Fergana State University, 2023)
In the article, the rhythm creates musicality, melodiousness, and emotionality based on rhythmic fragments and rhythmic tools in Uzbek lyrics of the period of independence. Psychological, structural-poetic, descriptive methods were used in the research. As a result of this, the harmony of rhythm, rhyme, and tone of the poetic speech with the thought and feeling of the poem in reaching the heart of the reader was proved by the example of the poetry of Abdulla Oripov, Erkin Vahidov, Halima Khudoyberdieva, Azam Oktam. The conclusions drawn on the basis of the scientific results of the research are the basis for the scientific-theoretical completion of the poetics of lyrical genres.